2015
DOI: 10.1016/j.diabet.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anxiety and depression among diabetic African patients in Guinea: Association with HbA1c levels

Abstract: Anxiety and depression symptoms in people with type T2D are common in Guinea. Urban residence, low socioeconomic status and high levels of HbA1c were significantly associated with a greater risk of anxiety and depression, highlighting the psychological burden related to diabetes in Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
4
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 40 publications
(49 reference statements)
6
41
4
1
Order By: Relevance
“…However, in some studies, women and married people are reported to be at a higher risk of depression. 18,21 In this study, those over 50 years of age, having low education level, unemployed, having three or more children and married to a husband with lower education level were determined to be at a greater risk of depression. The participants with three or more children were found to be at risk of depression 1.848 times more than were those with two or fewer children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in some studies, women and married people are reported to be at a higher risk of depression. 18,21 In this study, those over 50 years of age, having low education level, unemployed, having three or more children and married to a husband with lower education level were determined to be at a greater risk of depression. The participants with three or more children were found to be at risk of depression 1.848 times more than were those with two or fewer children.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (2008) and Camera et al (2014) found that the rate of depression was higher among patients using insulin. 21,30 Insulin administration is an invasive procedure, and thus those administering insulin should comply with certain rules. This may be difficult for patients and lead to exhaustion and hopelessness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies [4,8,9,11,13] were carried out on diabetes "type I", adolescent diabetes, or diabetes of both types ' I ' and ' II '. The present study aimed at patients with diabetic mellitus ' type II '.…”
Section: Discussionmentioning
confidence: 99%
“…According to studies, anxiety and depression result in high levels of glycosylated hemoglobin in blood [10,11]. There exist various cases where following psychological interventions, high levels of hemoglobin "A1c" were observed.…”
Section: Introductionmentioning
confidence: 99%